The Theory of Vibrational Oscillation of the Singing Voice - Sulaimonova, Gulorom Nematovna (European Journal of Life Safety and Stability (2660-9630), 2022)
The skillful use of the resonators of the singing apparatus is one of the most important aspects of vocals. For most vocalists, skill comes with experience. The ability to direct the sound in the right direction is an important condition for a vocalist. Possession of a point of support. The singer must be able to extract the sounds of the lower and upper positions. For this, head, chest resonators are used. Development of figurative thinking. The voice comes from the larynx, but the artist must imagine that the sounds originate in the chest, and only then break out. When performing high notes, tutors achieve lightness of sound, the feeling that the sound, penetrating through the soft palate, comes out of the crown of the head.